2003
DOI: 10.1023/a:1027383710582
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Excessive proliferation of vascular smooth muscle cells (VSMCs) is a critical element in the development of several vascular pathologies, particularly in atherosclerosis and in restenosis due to angioplasty. We have shown that butyrate, a powerful antiproliferative agent, a strong promoter of cell differentiation and an inducer of apoptosis inhibits VSMC proliferation at physiological concentrations with no cytotoxicity. In the present study, we have used cDNA array technology to unravel the molecular basis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 59 publications
1
19
0
1
Order By: Relevance
“…The amount of SCFA can be essentially influenced by three factors: diet composition, intestinal microbiota and intestinal area [108,109]. SCFA are not only considered an important substrate for the enterocytes, but are also able to modulate the inflammatory response [25,110,111]. Fig 6 shows SCFA concentration in the animals’ colon.…”
Section: Resultsmentioning
confidence: 99%
“…The amount of SCFA can be essentially influenced by three factors: diet composition, intestinal microbiota and intestinal area [108,109]. SCFA are not only considered an important substrate for the enterocytes, but are also able to modulate the inflammatory response [25,110,111]. Fig 6 shows SCFA concentration in the animals’ colon.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of our knowledge on regulatory impact of butyrate on global gene expression is derived from in vitro studies and observations 6,31,32. However, caution in interpretation of in vitro data and application of knowledge gained in vitro to in vivo models is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…SCFAs, such as butyrate, are known to promote rumen development and stimulate the proliferation of rumen epithelial cells in vivo 33. However, butyrate inhibits the proliferation of epithelial cells of the large intestine, rumen and kidney by down- regulating genes controlling cell proliferation in vitro 2,32. Butyrate also induces apoptosis and differentiation of tumor cells 34,35.…”
Section: Discussionmentioning
confidence: 99%
“…This was supported by our observation that the total number of genes transcribed in butyrate-treated cells (mean ± sd =19,322±155) was significantly higher than in untreated control cells (17,626±125) ( P <0.00001). Transcriptional effects of butyrate have been extensively investigated in various cell types, in both in vitro and in vivo models [19], [23][25]. Indeed, previous studies have demonstrated that butyrate down-regulates genes controlling cell proliferation in vitro , resulting in the inhibition of the proliferation of epithelial cells [25], [26].…”
Section: Discussionmentioning
confidence: 99%